Pengaruh Atmosphere Ritel Terhadap Keinginan Membeli Masyarakat Di Kota Padang - Heru Aulia Azman; Tri Rachmat Riski (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2016)
The atmosphere of retail shall function as a kind of stimuli that will attract the visitor to decide which store to choose. Further, it was aimed to evoke the desire of visitors to purchase and create transactions. The purpose of this study was to determine the impact of the atmosphere of retail on the intention to buy among visitors. Explanatory research and survey research was conducted by spreading 100 questionnaires to visitors. The result of the study found that (1) according to partially colour and display have significant influence toward intention to buy, and partially cleanness, music, smell, temperature, and lighting did not have significant influence toward intention to Â buy, and (2) in a manner of simulating the retail atmosphere has significant influence toward intention to buy